Réponses

2014-09-18T09:43:52+02:00

23)   A = 4/3 x 9/5 - 3/2                           B = 4/3 x (9/5 - 3/2)

         A = 36/15 - 3/2                               B = 4/3 - (18/10 - 15/10)

         A = 72/30 - 45/30                           B = 4/3 - 3/10

         A = 27/30                                        B = 40/30 - 9/30

         A = 9/10                                          B = 31/30


24)    A = (2/5 + 1/3) : 11/3                      B = 22/15 : 4/9 - 5/2

          A = (6/15 + 5/15) : 11/3                 B = 22/15 x 9/4 - 5/2

          A = 11/15 : 11/3                             B = 33/10 - 5/2

          A = 11/15 x 3/11                             B = 33/10 - 25/10

          A = 1/5                                            B = 4/5


25)     A = (5/2 - 7/4) : 3/8                          B =  (5/4 - 3) : (2 x 11/6)

          A = (10/4 - 7/4) : 3/8                        B = (5/4 - 12/4) : 11/3

          A = 3/4 x 8/3                                    B = -7 x 3/11

          A = 2                                                B = -21/11